The lichens and lichenicolous fungi of the Berezan Island with notes on its floristic and landscape diversity (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Forty three species of the lichens and five species of the lichenicolous fungi were found on the Berezan Island (Mykolaiv region, Ukraine). Lecania leprosa and Myriolecis bandolensis are the first time reported for Ukraine. Firstly, L. leprosa was found after diagnosis publish. M. bandolensis was distributed in Western Mediterranea, but the first time collected on Black Sea coast. The location of ephemeral lichen Epiphloea byssina is the second in steppe zone of Ukraine. It forms black crust on the cliff edges. In Ukraine, the island is a northern habitat for Collemopsidium halodytes that forms black zone in lower geolittoral zone. The lichens Athallia skii, Collemopsidium halodytes, Flavoplaca austrocitrina, F. limonia, Lecania inundata, Verrucula biatorinaria, Staurothele frustulenta and lichenicolous fungus Lichenochora caloplacae are new to Mykolaiv region. The limestone outcrops in geolittoral zone, branches of the shrubs (Kochia prostrata, Ephedra distachya) and soil in abrasion places are natural substrates for lichens. There are 50 % of species diversity here. The archeological artefacts (e.g. limestone walls, memorial stones), concrete builds are main substrates for lichens in island. Preliminary list of the vascular plants is 45 species from 40 genera, 20 familia and 2 division. The steppe species on the cliff edges are nature vegetation. Agropyron pectinatum, Festuca valesiaca (rare), Achillea setacea, Allium guttatum, Artemisia austriaca, Eryngium campestre, Salvia nemorosa, Poa bulbosa were dominate grass species on the island. Ephedra distachya is a species from Mykolaiv Red Data List. The illustrations of the island landscapes, lichens and vascular plants are given in the paper.
Keywords: geolittoral, cliff, limestone, concrete, Myriolecis bandolensis, Lecania leprosa.